The analysis of differences in technical and tactical elements of judo based on three women Balkan's championships - Torlakovic, A.; Kajmovic, H.; Radjo, I.; Kapo, S. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The objective of this research was conducted in order to determine the differences in technical and tactical elements of women judo fights on Balkan`s Championships and to compare levels of differences in using tactical and technical elements during competition activities. A sample of 137 judo matches on three Balkan`s Championships was used (2001/2002 and 2006). Methods In the purpose of analysis, we must introduce technical and tactical variables. For this research canonical discriminated analysis was used to determine the differences in particular situations (Rc, Wilk`s Lambda, Barttler`s test, Test of functions, Structure, Matrix, Chi-square). Results: The result of this analysis show that there are statistically significant differences between matches on Balkan`s Championships 2001/2002 and 2006. Summary of canonical discriminate functions show one isolated discriminated function. The x2 (Chi Square) test was used to determine the differences between indicators for situational efficiency. The results show statistically important differences between fights on tree Balkan`s Championships for: Place of attack on the tatami (x2 = 25.5; df = 1; p = 0.000) Technical points and penalties (x 2 = 27.0; df = 8; p = 0.001) Elapsed time (x2 = 9.36; df = 1; p = 0.002) Grips configuration (x2 = 7.75; df = 2; p = 0.021) Discussion: Main reason for those differences is changing of judo rules during 2002-2006 periods, made by IJF. According to them, there is no red square on tatami, penalties and match duration for women are changed and "gold point" is introduced. These parameters were gathered concerning real fight at the highest competitive level. Also, regarding all analyzed matches, the differences were noticed in frequency of used techniques between NAGE WAZA and KATAME WAZA groups. Given results might be used for programming and training process control improvement in judo for senior female fighters in Bosnia and Herzegovina and wider.